Characterization of an Atypical Metalloproteinase Inhibitors Like Protein (Sbp8-1) From Scallop Byssus - Zhang, Xiaokang; Dai, Xiaoting; Wang, Lulu; Miao, Yan; Xu, Pingping; Liang, Pengyu; Dong, Bo; Bao, Zhenmin; Wang, Shi; Lyu, Qianqian; Liu, Weizhi (Frontiers in Physiology, 2018)
Adhesion is a vital physiological process for many marine molluscs, including the mussel and scallop, and therefore it is important to characterize the proteins involved in these adhesives. Although several mussel byssal proteins were identified and characterized, the study for scallop byssal proteins remains scarce. Our previous study identified two foot-specific proteins (Sbp7, Sbp8-1), which were annotated as the tissue inhibitors of metalloproteinases (TIMPs). Evolutionary analysis suggests that the TIMP genes of Chlamys farreri had gone through multiple gene duplications during evolution, and their potential functional roles in foot may have an ancient evolutionary origin. Focusing on the Sbp8-1, the sequence alignment and biochemical analyses suggest that Sbp8-1 is an atypical TIMP. One significant feature is the presence of two extra free Cys residues at its C-terminus, which causes the Sbp8-1 polymerization. Considering the fact that the no inhibitory activity was observed and it is mainly distributed in byssal thread and plaque, we proposed that this atypical Sbp8-1 may play as the cross-linker in scallop byssus. This study facilitates not only the understanding of scallop byssus assembly, also provides the inspiration of water-resistant materials design.